" n Ontleding van die hoofstrominge van Bybelinterpretasie wat onderliggend is aan geloofsekerheid - Labuschagne, Kobus (HTS teologiese studies, 2001)
An analysis of three main streams in Biblical interpretation underlying the assurance of faith. This aricle reflects on the history of Biblical interpretaion and the foundations upon which assurance of faith has been built. It presents three main hermeneutical streams in the history of the church. These main streams can be described in terms of the emotional-mind, the intellectual-mind and the from-the-outside-liberated-mind.